Battling mosquito-borne diseases: Why it matters - Lindahl, Johanna F. (International Livestock Research Institute, 2019)
Johanna Lindahl, senior scientist at ILRI and coordinator of the ‘Metropolitan Mosquito’ project, share tips on how to avoid mosquito bites and keep people away from deadly mosquito-borne diseases like dengue and Japanese encephalitis.